Glucocorticoid Resistance: Is It a Requisite for Increased Cytokine Production in Depression? A Systematic Review and Meta-Analysis - Perrin, Andrew J.; Horowitz, Mark A.; Roelofs, Jacob; Zunszain, Patricia A.; Pariante, Carmine M. (Frontiers in Psychiatry, 2019)
Glucocorticoid resistance – reduced function of the glucocorticoid receptor (GR) – is seen in many depressed patients. It is argued that this resistance to glucocorticoids leads to failure of normal feedback regulation on the immune system. High levels of pro-inflammatory cytokines result. We sought to identify evidence supporting or refuting a link between glucocorticoid resistance and immune dysregulation in depression, and to summarize retrieved evidence in aggregate form. Methods: We systematically reviewed and meta-analysed studies that examined cytokine levels in depressed patients compared with controls and that also reported a measure of glucocorticoid resistance. These measures included plasma cortisol, the dexamethasone suppression test (DST), GR expression levels and the results of in vitro assays of GR function. We conducted four separate meta-analyses to test for moderating effects of glucocorticoid resistance on cytokine production in depression. After sub-grouping 32 studies by the ratio of cortisol levels in patients compared with controls, we observed a trend for increasing glucocorticoid resistance (i.e., the most hypercortisolemic patients) to be associated with increased production of IL-6 [d = 0.94; 95% CI (0.29, 1.59)] and TNF-α [d = 0.46; 95% CI (0.12, 0.79)]. We stratified 9 studies that reported DST results by relative glucocorticoid resistance between patients and controls, identifying a trend for higher glucocorticoid resistance in patients, compared with controls, to be associated with higher cytokine production in patients (170 patients and 187 controls). This was particularly evident when studies were sub-grouped by source of cytokine – plasma [d = 1.04; 95% CI (0.57, 1.50)] versus in vitro [d = 0.24; 95% CI (-0.20, 0.67)]. Stratifying the 4 studies (147 patients and 118 controls) that used in vitro assays of GR function or GR expression to quantify glucocorticoid resistance revealed variable contributions to cytokine production in patients compared with controls [overall effect size d = 1.35; 95% CI (0.53, 2.18)]. Our work provides some support for a model conceptualizing glucocorticoid resistance as a requisite for increased inflammation in depression. The limited number of studies identified highlights the need for purpose-designed investigations that directly examine the relationship between glucocorticoid resistance and cytokine production in depression.